1991
DOI: 10.1111/j.1749-6632.1991.tb37869.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Factors Influencing Growth and Maintenance of Endometriosisa

Abstract: The unpredictable response of endometriosis to steroids and its recurrence after therapy, led us to hypothesize a possible further control of this pathology by factors other than steroids. The presence of estrogen, progesterone and epidermal growth factor receptors (ER, PR, EGFr) was evaluated using immunohistochemistry before and after therapy with Danazol or a gonadotropin-releasing hormone analogue (GnRHa), Buserelin. EGFr, ER and PR were present in 100% of endometrial specimens, and in 71%, 29% and 49% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 24 publications
(2 reference statements)
0
19
0
Order By: Relevance
“…However, retrograde menstruation occurs in up to 80% of reproductive-age women; the discrepancy between the incidence of this phenomenon and the occurrence of pelvic endometriosis (10%-20%) might be explained by the presence of other permissive factors that promote the implantation and growth of endometrial cells (3). A growing body of evidence indicates that a combination of genetic, hormonal, immunologic, and environmental factors seem to be involved in the pathogenesis of this enigmatic disorder (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 95%
“…However, retrograde menstruation occurs in up to 80% of reproductive-age women; the discrepancy between the incidence of this phenomenon and the occurrence of pelvic endometriosis (10%-20%) might be explained by the presence of other permissive factors that promote the implantation and growth of endometrial cells (3). A growing body of evidence indicates that a combination of genetic, hormonal, immunologic, and environmental factors seem to be involved in the pathogenesis of this enigmatic disorder (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 95%
“…Retrograde menstruation occurs in up to 80% of women during their reproductive life; the discrepancy between the incidence of this phenomenon and the occurrence might be explained by the presence of further 'permissive' factors that promote the ectopic implantation and growth of endometrial cells. 2 The involvement of chemokines in endometriosis is becoming more evident as current research progresses. Chemokines have the ability to attract and activate inflammatory cells.…”
Section: Introductionmentioning
confidence: 99%
“…Dioxin (2,3,7, TCDD), an air pollutant, and estrogen also appear to be involved in endometriosis. Both endometrial stromal cells (ESCs) and the combination of 17b-estradiol and TCDD increase the secretion of TECK in the endometriosis-associated cells and promote the invasiveness of ESCs by increasing expression of matrix metalloproteinase (MMP)-2 and MMP-9.…”
mentioning
confidence: 99%
“…Although molecular mechanisms remain to be defined, an increasing body of data suggests the possible transformation of endometriotic cells in endometrioid or clear cell carcinoma [14]. In addition, one EGFR gene polymorphism has been recently associated with susceptibility to endometriosis [15], and Melega et al reported that about 21% of endometriosis are EGFR positive and oestrogen receptor negative, suggesting a potential role of epidermal growth factor in the growth and maintenance of endometrial ectopia [16]. Finally, the development of new therapeutic agents targeting EGFR has attracted attention to treat various HER positive tumours.…”
Section: Introductionmentioning
confidence: 99%